Analisis Faktor-Faktor yang Mempengaruhi Minat Mahasiswa Akuntansi Terhadap Pemilihan Profesi Akuntan Publik (Studi Kasus pada Mahasiswa Akuntansi FEB Universitas Islam Malang Angkatan 2019) - Pratama, Riko Henry; Maslichah, Maslichah; Afifudin, Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The purpose of this study was to analyze and examine the factors that influence accounting students' interest in choosing the accounting profession. This study uses a quantitative approach. The location of this research was conducted at the Faculty of Economics and Business, Islamic University of Malang. This research will be conducted in February 2022 until completion. The population in this study were FEB students majoring in accounting class of 2019 at the Islamic University of Malang. Sampling was carried out using purposive sampling method, with predetermined criteria so that 183 samples were obtained. The results of the study stated that partially and simultaneously Financial Rewards, Labor Market Considerations, Work Environment, Professional Recognition and Family Environment on the interest of accounting students to become accountants.Keywords: Financial rewards, labor market considerations, work environment, professional recognition and family environment & interest in accounting students to become accountants.